Understanding Nursing Resilience During the COVID-19 Pandemic Through Narrative and Art: A Feminist Exploration in Educational Research - Flegg, Carol (Art/Research International)

(untitled) (University of Alberta, 2024)
The resilience and retention of nurses is a complex and urgently compelling phenomenon in the global context, made even more critical given the challenges of the COVID-19 pandemic. This study explored the stories of nursing resilience told from the perspective of four public health nurses who worked during the COVID-19 pandemic, utilizing narrative inquiry and arts-based research underpinned by the feminist theoretical framework. The stories of nursing resilience were shared in group discussions, one-on-one conversations, and artistic collages with artist statements; these articulated the nurses’ thoughts and feelings about resilience while working during the pandemic. Elucidated are the impacts of the institutional power structure in nursing, thoughts on using artistic expression, and images of a black cloud to express nursing resilience. Further research is implicated on the use of art in nursing education, the power structure in health care, and nurses feeling valued by the healthcare institution.